2014
DOI: 10.1007/s00737-014-0478-8
|View full text |Cite
|
Sign up to set email alerts
|

Personality and risk for postpartum depressive symptoms

Abstract: Postpartum depression (PPD) is a common childbirth complication, affecting 10-15 % of newly delivered mothers. This study aims to assess the association between personality factors and PPD. All pregnant women during the period September 2009 to September 2010, undergoing a routine ultrasound at Uppsala University Hospital, were invited to participate in the BASIC study, a prospective study designed to investigate maternal well-being. Depressive symptoms were assessed with the Edinburgh Postnatal Depression Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 56 publications
1
44
0
2
Order By: Relevance
“…The self-report questionnaire SSP consists of 91 items grouped into 13 different scales [19] [25][26][27], similar internal consistencies [19,21,22,25], similar factor loadings between different samples [19,21,22,40,41] and conformity with other personality constructs has been documented [21].…”
Section: Psychometric Instrumentsmentioning
confidence: 99%
“…The self-report questionnaire SSP consists of 91 items grouped into 13 different scales [19] [25][26][27], similar internal consistencies [19,21,22,25], similar factor loadings between different samples [19,21,22,40,41] and conformity with other personality constructs has been documented [21].…”
Section: Psychometric Instrumentsmentioning
confidence: 99%
“…Personality disorders existing prior to conception were demonstrated to be related to anxious and depressive symptoms in pregnancy, independently of the effect of coexisting mood or anxiety disorders 13 . Neuroticism, which has been previously identified as a risk factor, was also affirmed to confer significant risk for postpartum depression in a prospective study of 1,037 non-depressed pregnant women 14 .…”
Section: Part I: Advances In Understanding Epidemiology Phenomenologmentioning
confidence: 69%
“…Also note that most anxiety research has been done on mothers and women, and that less is known about paternal stress experiences during the prenatal period. Nevertheless, some studies have shown that depressed and anxious fathers during pregnancy experience similar symptoms as those reported by depressed mothers (Field et al., ; Field et al., ) while other studies have noted that paternal anxiety may increase the risk of developing depression (Iliadis et al., ).…”
Section: Prenatal Mental Health and Paternal Stressmentioning
confidence: 97%